Genera of euophryine jumping spiders (Araneae: Salticidae), with a combined molecular-morphological phylogeny - Zhang, Junxia; Maddison, Wayne P. (Zootaxa, 2015)
Morphological traits of euophryine jumping spiders were studied to clarify generic limits in the Euophryinae and to permit phylogenetic classification of genera lacking molecular data. One hundred and eight genera are recognized within the subfamily. Euophryine generic groups and the delimitation of some genera are reviewed in detail. In order to explore the effect of adding formal morphological data to previous molecular phylogenetic studies, and to find morphological synapomorphies, eighty-two morphological characters were scored for 203 euophryine species and seven outgroup species. The morphological dataset does not perform as well as the molecular dataset (genes 28S, Actin 5C; 16S-ND1, COI) in resolving the phylogeny of Euophryinae, probably because of frequent convergence and reversal. The formal morphological data were mapped on the phylogeny in order to seek synapomorphies, in hopes of extending the phylogeny to include taxa for which molecular data are not available. Because of homoplasy, few globally-applicable morphological synapomorphies for euophryine clades were found. However, synapomorphies that are unique locally in subclades still help to delimit euophryine generic groups and genera. The following synonyms of euophryine genera are proposed: Maeotella with Anasaitis; Dinattus with Corythalia; Paradecta with Compsodecta; Cobanus, Chloridusa and Wallaba with Sidusa; Tariona with Mopiopia; Nebridia with Amphidraus; Asaphobelis and Siloca with Coryphasia; Ocnotelus with Semnolius; Palpelius with Pristobaeus; Junxattus with Laufeia; Donoessus with Colyttus; Nicylla, Pselcis and Thianitara with Thiania. The new genus Saphrys is erected for misplaced species from southern South America.